Horizontal Inequities in the uptake of Hospital Delivery and the Role of Social Determinants in China - Lin Feng Xing; Zhang Yaoguang; Xu Ling; Guo Yan (Journal of Women's Reproductive Health, 2016)
Objectives: To measure the horizontal inequity in the uptake of hospital delivery and quantify the contribution of various social determinants of health (SDH) to such inequity in China from 1993-2008 Methods: With four national representative surveys in China conducted in 1993, 1998, 2003 and 2008, we measured horizontal inequity in the uptake of hospital delivery using indirect standardized concentration indices (CIs). By decomposing Cis into components, we explored the contributions of income, health insurance, education, living conditions to such inequities. Oaxaca type decomposition was further used to explain the role for each SDH on the changes of inequities between 1993 and 2008. Results: We found that horizontal inequity in the coverage of hospital delivery approached equal line in the urban areas and shrank by 90% in rural China in 1993-2008. The data also showed that dramatic socio-economic achievement was made across the 16 years, including education, income, health insurance and living conditions, which contributed substantially to the reduction of the inequities in the uptake of hospital delivery. Income’s contribution was mainly made by its protection effect, while health insurance’s role was mainly played by its equal distributions in the rural areas. Conclusions: The horizontal inequity in the uptake of hospital births vanished in urban China and decreased in the rural. The leading contributors to such inequity were income, health insurance, living conditions and education. Decomposition analysis suggests that more investments are warranted for financial risk protection and targeted demand side subsidies may make a difference.
Keywords: Horizontal Inequity